2011
DOI: 10.1364/oe.19.005760
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of the birth of an optical vortex using diffraction from a triangular aperture

Abstract: The study and application of optical vortices have gained significant prominence over the last two decades. An interesting challenge remains the determination of the azimuthal index (topological charge) ℓ of an optical vortex beam for a range of applications. We explore the diffraction of such beams from a triangular aperture and observe that the form of the resultant diffraction pattern is dependent upon both the magnitude and sign of the azimuthal index and this is valid for both monochromatic and broadband … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
55
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(56 citation statements)
references
References 19 publications
1
55
0
Order By: Relevance
“…Other methods have also been introduced to measure the OAM of optical vortices based on the diffraction phenomena [12][13][14]. More recently, it has been shown that a triangular aperture illuminated with a vortex beam creates a truncated lattice diffraction pattern and that the resultant diffraction pattern can be used to measure the OAM of light beams [15][16][17]. Other methods for measuring the topological charge of an optical vortex have included the diffraction intensity pattern after an axicon [18] or an annular triangle aperture [19].…”
mentioning
confidence: 99%
“…Other methods have also been introduced to measure the OAM of optical vortices based on the diffraction phenomena [12][13][14]. More recently, it has been shown that a triangular aperture illuminated with a vortex beam creates a truncated lattice diffraction pattern and that the resultant diffraction pattern can be used to measure the OAM of light beams [15][16][17]. Other methods for measuring the topological charge of an optical vortex have included the diffraction intensity pattern after an axicon [18] or an annular triangle aperture [19].…”
mentioning
confidence: 99%
“…As far, the aperture diffraction or transmission has been applied in different fields, such as the scanning optical microscopy [3], the enhanced transmission [1,4], the birth of optical vortex [5], and so on. As we know, the spatial distribution of diffraction field depends on the shape and the size of aperture, so the diffraction of the aperture with different shape, such as square aperture [4], triangular aperture [1,5], circular aperture [6][7][8][9][10] and elliptical aperture [11][12][13], has been deeply studied. In most studies including our former work, for simplifying theoretical analysis of the aperture diffraction, the edges of aperture are considered to be perfectly regular.…”
Section: Introductionmentioning
confidence: 99%
“…Recently further experimental demonstrations of the generation of such vortices have appeared [10,13,14,16]. A pair of cylindrical lenses can be used to convert a laser-generated Hermite-Gaussian (HG) mode into a Laguerre-Gaussian (LG) mode carrying orbital angular momentum [14].…”
mentioning
confidence: 99%